Biddo: Property Rental Bidding System - Yi Wen, Lui; Suhaila Mohd Yasin (Applied Information Technology And Computer Science, 2025)
In the digital era, where data management is obviously crucial, this project focuses on addressing the operational challenges faced by the case study, a Malaysian real estate agency offering a range of business services through offline and online channel. However, the agency’s current manual data recording and storage methods have led to potential inconsistencies and data loss. To tackle these issues, a property rental bidding system called “Biddo” is developed using a structured approach and guided by the Evolutionary Prototyping model. The system stands out as it offers easy registration, property search, and a seamless bidding process for users. The system aims to enhance business operation efficiency and provide a seamless property rental experience through bidding, thereby improving the customer satisfaction. The project’s significance lies in its potential to revolutionize the property rental industry, particularly benefiting those with limited on-campus housing options.